Impact of Aquarius Sea-Surface Salinity Assimilation in Improving the Ocean Analysis Over Indian Ocean. Issue 2 (4th March 2018) - Seelanki, Vivek; Sreenivas, P.; Prasad, K. V. S. R.
ABSTRACT: The distribution of ocean salinity controls the density field and thereby plays a major role in influencing the ocean dynamics. It has been a challenging task to understand the variability of salinity structure in the regions of large fresh water discharge and high precipitation such as Bay of Bengal (BoB). Recent advancement in satellite technology has made possible the measurement of sea surface salinity (SSS). Aquarius is the satellite which measured the global SSS for the period 2011 to 2015. In the present study, we assimilated Aquarius SSS in the Global Ocean Data Assimilation System based on 3DVAR technique. The assimilation of Aquarius SSS resulted in reduced biases in salinity not only at the surface, but also in the vertical distribution of salinity and better captured the temporal variations of salinity structure in sensitive regions, such as the Bay of Bengal. In addition, the assimilation of SSS showed marginal improvement in ocean thermal structure over data sparse regions of Indian Ocean. It is also shown that the assimilation of Aquarius SSS has improved the stratification in the upper Ocean which is the key factor in the observed improvement in ocean analysis.